An explorative cross-sectional study on breast-feeding practices among children aged 12-23 months residing in a district of northwestern Punjab: an urban-rural comparison - Kaur, Kirandeep; Kaur, Jasleen; Mahajan, Sanjeev; Padda, Preeti (International Journal Of Community Medicine And Public Health, 2024)
Background: The IYCF guidelines clearly dictates the breastfeeding practices for first six months of life. But, the practical adoption of these recommendations continues to fall short of expectations. Factors like urbanization, infant formula marketing, and maternal employment have contributed to declining exclusive breastfeeding (EBF) rates. Therefore, we planned to conduct this study to assess breastfeeding practices during first 6 months of life and made an urban-rural comparison. Methods: An explorative cross-sectional study was conducted in 2 villages and 2 urban slums, involving 420 mother-child pairs (210 each from rural and urban). A mother and child duo where child was aged between 12-23 months were interviewed. The information pertaining to breastfeeding during first six months were collected on pre-designed, pretested and validated proforma. Data was compiled and analysed using Epi-info 0.7. Results: Out of 420 participants 54% were males and 46% were females. Breastmilk was given to 98% of the study participants with no significant urban-rural difference. However, only 5% of urban and 2% of rural infants started breastfeeding within the first hour after birth. Overall, 46% of infants began breastfeeding two days after birth, with a significantly higher proportion in rural areas (53%) compared to urban areas (39%).74% were exclusively breastfed. Prelacteal feeding was significantly more common in rural areas (87%) than in urban areas (76%). Conclusions: While exclusive breastfeeding rates were relatively good. Significant differences were observed in early breastfeeding initiation and prelacteal feeding in rural and urban area.